Pengukuran dan analisa efektivitas mesin pencetak paving menggunakan metode overall equipment effectiveness (OEE) - Indira Kusuma Wardani; Fransiskus Tatas Dwi Atmaji; Judi Alhilman (Journal Industrial Servicess, 2021)
Machine effectiveness is one of the important factors in the production process in a manufacturing company to produce goods. The paving molding machine is one of the machines used to produce black paving at PT XYZ. Based on historical data from the Engineering Maintenance Department, this machine has the highest breakdown frequency which has an impact on the low effectiveness and productivity of the machine. To overcome this problem, an analysis of the effectiveness of the paving molding machine was carried out using the Overall Equipment Effectiveness (OEE) method. OEE aims to analyze machine indicators, which consist of machine availability, performance efficiency, and the quality level of the machine's production. The results of the OEE analysis show that the value of the paving molding machine is 68.18% and is still below the Japan Institute of Plant Maintenance standard of 85%. Six Big Losses is used to determine the low OEE value arising from the production process, on the paving molding machine. From the results of the analysis, two dominant loss factors have the most influence on the effectiveness of the paving molding machine, namely the high value of reduced speed loss (51.92%) and idling and minor stoppages loss (23.69%). These two dominant loss factors are then analyzed using a fishbone diagram to obtain the root causes and proposed solutions.